(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study examines the adoption of electric scooters, emphasizing the factors influencing consumers’ purchase decisions and post-purchase satisfaction. It explores key determinants such as cost, range, charging infrastructure, design, and environmental benefits, while also addressing challenges like high initial investment and inadequate charging facilities. Data were collected from 50 electric scooter users in Alappuzha using a structured questionnaire. The findings offer valuable insights for manufacturers and policymakers to enhance electric scooter adoption and user satisfaction, thereby supporting the transition toward sustainable urban mobility.